Inclusion of women in peace processes: The case of Colombia - Mejia, Andrea C. (Tufts Archival Research Center, 2022)
The international binding normative establishes the obligation for member states to include women in all peace development processes. That implies physical inclusion by assigning women to official leadership positions and intellectual inclusion by incorporating their perspectives and contributions. A more progressive approach includes the incorporation of gender mainstreaming in the peace accords. However, without trying to equate the gender approach with the inclusion of women, this work focuses on women. Given that the Colombian peace agreement has been recognized for the inclusion of a gender approach, this work tries to identify to what extent the Colombian case incorporated women in developing the peace agreement between the Government and the FARC, signed in 2016.; Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy.; Submitted to the Fletcher School of Law and Diplomacy.